(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Stroke is considered as one of the major causes of physical disability which has a serious impact on mental health and affecting the quality of life (QoL) of an individual. This study is intended to explore the effect of Mamsyadi kwatha along with structured module for addressing the psychological problems of stroke survivors and to measure its effects on improving the issues like depression, anxiety, anger proneness, fatigue, emotional incontinence and quality of life in them. Mamsyadi kwatha with proven efficacy in anxiety and depression was selected with the structured Satvavajaya module and administered in 21 participants. The participants were in the age group of 30-75 without any history of psychiatric illness and recent stressful life events or trauma and those who can communicate properly were recruited for the study. Mamsyad kwatha and Satvavajaya module were administered for initial 14 days. Assessments were done on 0th day/ 7th day/ 15th. Main outcome measures included emotional problems like depression and anxiety, fatigue, emotional incontinence, anger proneness and stroke related QoL. After the treatment, significant improvements were noted in depression (p<0.001), anxiety (p<0.001), anger proneness (p<0.001) and in majority of the domains in SSQoL (p<0.001)- quality of life.